Genome Evolution and Introgression in the New Zealand mud Snails Potamopyrgus estuarinus and Potamopyrgus kaitunuparaoa - Fields PD; Jalinsky JR; Bankers L; McElroy KE; Sharbrough J; Higgins C; Morgan-Richards M; Boore JL; Neiman M; Logsdon JM (Oxford University Press on behalf of Society for Molecular Biology and Evolution, 2024)
We have sequenced, assembled, and analyzed the nuclear and mitochondrial genomes and transcriptomes of Potamopyrgus estuarinus and Potamopyrgus kaitunuparaoa, two prosobranch snail species native to New Zealand that together span the continuum from estuary to freshwater. These two species are the closest known relatives of the freshwater species Potamopyrgus antipodarum-a model for studying the evolution of sex, host-parasite coevolution, and biological invasiveness-and thus provide key evolutionary context for understanding its unusual biology. The P. estuarinus and P. kaitunuparaoa genomes are very similar in size and overall gene content. Comparative analyses of genome content indicate that these two species harbor a near-identical set of genes involved in meiosis and sperm functions, including seven genes with meiosis-specific functions. These results are consistent with obligate sexual reproduction in these two species and provide a framework for future analyses of P. antipodarum-a species comprising both obligately sexual and obligately asexual lineages, each separately derived from a sexual ancestor. Genome-wide multigene phylogenetic analyses indicate that P. kaitunuparaoa is likely the closest relative to P. antipodarum. We nevertheless show that there has been considerable introgression between P. estuarinus and P. kaitunuparaoa. That introgression does not extend to the mitochondrial genome, which appears to serve as a barrier to hybridization between P. estuarinus and P. kaitunuparaoa. Nuclear-encoded genes whose products function in joint mitochondrial-nuclear enzyme complexes exhibit similar patterns of nonintrogression, indicating that incompatibilities between the mitochondrial and the nuclear genome may have prevented more extensive gene flow between these two species.
Keywords: Potamopyrgus; gastropod evolution; introgression; Animals; Snails; Phylogeny; New Zealand; Genetic Introgression; Evolution, Molecular; Genome, Mitochondrial; Genome